(untitled) (Fiep Bulletin - online, 2024)
Objective: to evaluate the influence of body composition on the performance of functional tests and on glycemic levels in adults with Down syndrome. Methods: 19 adult volunteers aged 18 to 49 years participated in the study. Fasting blood glucose, blood pressure, heart rate, handgrip strength, agility, dynamic balance and gait quality were evaluated. BMI, percentage of body fat, fat weight and lean weight were estimated using a mathematical equation. Results: The volunteers showed poor performance in functional tests. Moderate positive correlations and a small effect size were observed between body weight and body fat percentage (r = 0.0493; p = 0.032; d = 0.2430), and body fat percentage and blood glucose (r = 0.517; p = 0.028; d = 0.2670). In addition to strong positive correlations and moderate effect size between weight and fat weight (r = 0.846; p = 0.000; d = 0.7157) and lean weight with handgrip strength (r = 0.634; p = 0.004; d = 0.4019). The coefficient of determination between percentage of body fat and blood glucose (R2 = 0.2668) and lean weight and handgrip strength (R2 = 0.4019) was calculated. Conclusion: Body composition influenced the performance of functional tests and the volunteers’ glycemic levels. Furthermore, the body composition profile, characterized by BMI and high fat percentage, indicated a risk for the development of type 2 diabetes, as evidenced by the glycemic values collected.